Browsable TIF-Seq2 tracks from K562 after imatinib treatment - Pelechano, Vicent; Wang, Jingwen; Li, bingnan; Marques, Sueli (Karolinska Institutet, 2020)
Browsable dataset containing transcript boundaries for the manuscript:
Jingwen Wang, Bingnan Li, Sueli Marques, Lars M Steinmetz, Wu Wei, Vicent Pelechano, TIF-Seq2 disentangles overlapping isoforms in complex human transcriptomes, Nucleic Acids Research, Volume 48, Issue 18, 09 October 2020, Page e104, https://doi.org/10.1093/nar/gkaa691
The alignment files contains sequences of K562 cells using TIF-Seq2 method. The sequencing reads were aligned to the human reference genome hg38. Each read pair represents the boundary of an individual transcript. The first reads in pairs are 5' ends, while the second reads in pairs are 3' ends. The alignment files can be loaded into IGV for visualization. You can set up view as pairs in the alignment track.
Source code for the associated manuscript is available from GitHub at https://github.com/jingwen/TIFseq2
Raw data is deposited at GEO with access code GSE140912
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik